ANALISIS FAKTOR HEAD LOSSES PIPA PESAT TERHADAP DAYA YANG DIHASILKAN PEMBANGKIT LISTRIK TENAGA AIR (PLTA) PARAKAN KONDANG - Holik, Abdul; Muhamad Yunus, Riza (Universitas Majalengka, 2019)
The pipe is a closed channel which is usually circular in shape which is used to flow the fluid with a full flow section. Fluid flow that is in a closed pipeline, both laminar and turbulent flow types, must have suffered head losses. Head loss is caused by friction losses in the pipes, reducers, valves and others. Saguling Hydroelectric Power Plant itself has 2 rapid pipes (penstock) which have an important role as a distributor of water /discharge potential energy into kinetic energy to drive turbines using the heads of each unit. calculation of losses arising from the factors - the above factors need to be analyzed to provide input output as well as reference information regarding penstock head losses that occur in the rapid pipe (penstock) in the Parakan Kondang Hydroelectric Power Plant. The resulting head losses can be a reference to one of the factors that affect the performance of the turbine generator, which can be seen from the amount of power reduction generated.